2004
DOI: 10.1128/aem.70.4.2240-2244.2004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the Genes Encoding Propionicin T1 andProtease-Activated Antimicrobial Peptide and Their Expressionin ClassicalPropionibacteria

Abstract: The purpose of this study was to investigate the frequency of production of the bacteriocin propionicin T1 and the protease-activated antimicrobial peptide (PAMP) and their corresponding genes in 64 isolates of classical propionibacteria. This study revealed that these genes are widespread in Propionibacterium jensenii and Propionibacterium thoenii but absent from the remaining species of classical propionibacteria that were studied. The pro-PAMP-encoding gene (pamA) was found in 63% of the P. jensenii strains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 31 publications
0
9
0
2
Order By: Relevance
“…It is possible that the mature form of PAMP is produced via proteolytic cleavage of the proprotein by a hitherto undisclosed protease (11). The production of propionicin T1 and pro-PAMP is prevalent in P. jensenii and P. thoenii strains but has not been identified as occurring in P. freudenreichii (12). In fact, no bacteriocin has been purified from P. freudenreichii, although the antimicrobial potential of this organism has frequently been demonstrated (1,19,31).…”
mentioning
confidence: 99%
“…It is possible that the mature form of PAMP is produced via proteolytic cleavage of the proprotein by a hitherto undisclosed protease (11). The production of propionicin T1 and pro-PAMP is prevalent in P. jensenii and P. thoenii strains but has not been identified as occurring in P. freudenreichii (12). In fact, no bacteriocin has been purified from P. freudenreichii, although the antimicrobial potential of this organism has frequently been demonstrated (1,19,31).…”
mentioning
confidence: 99%
“…A recent survey on the prevalence of the pctA gene revealed that 13 of 24 P. jensenii strains contained this gene. However, only five strains produced antimicrobial activity corresponding to propionicin T1 (8). Intriguingly, six of the propionicin T1-negative P. jensenii strains contained a G3A transition mutation in the pctA gene, resulting in the amino acid substitution G 55 D in the mature bacteriocin (8).…”
Section: Resultsmentioning
confidence: 98%
“…However, only five strains produced antimicrobial activity corresponding to propionicin T1 (8). Intriguingly, six of the propionicin T1-negative P. jensenii strains contained a G3A transition mutation in the pctA gene, resulting in the amino acid substitution G 55 D in the mature bacteriocin (8). In order to investigate the biological activity of this propionicin T1 variant, the mutated gene (pctA-A) was cloned under the control of the P 4E promoter in the pAMT1 vector.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most strains of P. jensenii and P. thoenii produce and export the pro-PAMP protein, which is has no antimicrobial activity (31). However, the antimicrobial activity is produced extracellularly via proteolytic processing of the N-terminal part of the proprotein of the protease-activated antimicrobial peptide (PAMP).…”
Section: Figmentioning
confidence: 99%